الوقف على البحث العلمي : مقاصده وآلياته وتطبيقاته - حاج إبراهيم، بعمارة (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Islamic endowment (Waqf) is a fundamental financial resource for funding various social and scientific activities with a symbiotic dimension within the community. Of these activities scientific research funding, which is undergoing a shortage of funding and development at the Islamic world level due to shortage in funds allocations, this attributes to it not being considered as a national and developmental priority. Waqf offers an alternative and strategic funding resource for scientific research. This study addresses its purposes (Maqasid), mechanisms, and its applications in five chapters. The first chapter is an introduction to Waqf, whereas the second chapter presents the concept of Waqf and its relation to scientific research in terms of legitimacy and rooting. The third chapter is devoted to address the general and special dimensions of Maqasid in light of scientific research. The fourth chapter presents a number of jurisprudential mechanisms to operationalize Waqf in light of practical research as well as how to expand its size. The fifth chapter addresses the different fields of scientific research that can be funded through Waqf, in addition to its link to funding bodies; it also presents some temporary application cases such as the application of Waqf to scientific research. This study employs inductive approach for collecting information, analytical approach for analyzing texts and scholars' opinions in various research issues and analyzing field experiments, and field study to observe contemporary experiments of endowment applicability to scientific research. The findings of the study emphasize that Waqf is a fundamental funding tool for scientific research and it is obligatory competence. The nation (Ummah) is highly encouraged to pay special attention to its applicability, each individual according to its level and capability. Waqf is one of the priorities of development and civilization; it is also an effective tool in achieving the different purposes of Islamic law (Shariah) such as sustainable development and the establishment of the nation's system, save its existence, and achieve succession and civilization presence. Endowments of scientific research can be established through various forms such as endowment funds, endowment-based stock and endowment-based sukuk, and benefit from public endowments and unused endowments in order to expand its size. In this regard, contemporary experiments have proved that Waqf is an instrument with an effective and unlimited funding capacity; it is also complementary to various other sources of funding for scientific research and is not a substitute for them.